ASPECTOS PROCEDIMENTALES DE LA EXPROPIACIÓN EN LA NUEVA LEY DE LA REFORMA AGRARIA - Bejarano Guzmán, Ramiro (Revistas ICDP, 2015)
ASPECTOS PROCEDIMENTALES DE LA EXPROPIACIÓN EN LA NUEVA LEY DE LA REFORMA AGRARIA